Nutritional composition has limited impact on the foraging patterns of Northern Plains Gray Langurs (Semnopithecus entellus) (Bangladesh Journal of Zoology, 2025)
Along with the feeding behaviour, understanding the nutritional requirements of a threatened species can aid in effective conservation strategies. This study aimed to analyze whether the nutritional properties of food items correlate with the time spent feeding in Northern Plains Gray Langurs (Semnopithecus entellus). We studied eight groups of Langurs living in the non-forested area of Jessore, Bangladesh, from September 2012 to August 2013. Data on time spent feeding was collected through 10-minute continuous focal animal sampling from a total of 303 observation hours. Meanwhile, food items consumed by langurs, were collected from their habitat and afterwards, nutritional properties were analyzed from the food science laboratory of the Institute of Nutrition and Food Science (INFS) and the Center for Advanced Research in Sciences (CARS), University of Dhaka. The results showed that there were marked differences in protein, fat, carbohydrate, ash, and moisture content among food items of different plant species. We correlated the nutritional properties of analyzed food items with the time spent feeding on those particular food items. None of the nutritional content in food items significantly correlates with the langurs’ feeding time spent on particular food items. The findings suggest that langurs exhibit opportunistic feeding behaviour, prioritizing accessibility over macronutrient contents. Additionally, other factors such as food availability, seasonal variation, secondary metabolites, and social dynamics may play a critical role in shaping langurs feeding patterns. Therefore, future research on ecological and physiological factors, along with the other nutritional composition, such as fiber content and secondary metabolites, should be considered in order to better understand langurs’ dietary decisions.Bangladesh J. Zool. 53(1): 45-56, 2025